Strategi Kepala Sekolah dalam Meningkatkan Mutu Layanan Administrasi di SMA Negeri 6 Kota Jambi - Sinaga, Amanda Septianti; Zaskia, Lisa; Rahman, K.A; Pratama, Robin (Jurnal Pendidikan Tambusai, 2026)
The research background highlights the critical role of high-quality administrative services in supporting effective educational processes, with school principals playing a strategic leadership role. Objectives include identifying the principal's strategies, challenges, and solutions to improve administrative service quality at SMA Negeri 6 Kota Jambi. This qualitative case study employed purposive sampling from the school staff population, focusing on the principal, head of administration subsection, and administrative staff. Instruments comprised structured interviews, non-participant observation, and document analysis, processed via Miles & Huberman model (data reduction, display, and verification) with source triangulation. Findings reveal strategies such as integrated planning, SOP implementation, and service digitalization, hindered by limited honorary staff and technology adaptation issues. The conclusion asserts that participatory approaches and motivational incentives effectively address constraints, yielding more efficient services.